Does Media Matter? - Rejoice Tobias-Mamina; Eugine Tafadzwa Maziriri; Norman Chiliya (Communicare)
This study determined the direct effect and mediating effect of the presidential candidate’s perceived image, attitude towards voting and perceived image of the political party on the relationship between digital media exposure and voting intention. A quantitative research approach was utilised. Of the 350 questionnaires distributed, 302 usable self-administered questionnaires were retrieved for the final data analysis, representing a response rate of 87 percent. Partial least Squares Structural Equation Modeling (PLS-SEM) was employed in the data analysis. Significant relationships were found between the presidential candidate’s perceived image and attitude towards voting and between attitude towards voting and voting intention. Important to note about the study findings is that the mediating variables perceived image of the presidential candidate, perceived image of the political party and attitude towards voting partially mediates digital media exposure and voting intention relationship. This study contributes new knowledge to the existing body of digital media literature in Africa - a context that is often most neglected by some researchers in developing countries.